2020
DOI: 10.1016/j.nmni.2020.100747
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine is protective to the heart, not harmful: a systematic review

Abstract: Hydroxychloroquine (HCQ) has been shown to be at least somewhat effective in treating patients with coronavirus disease 2019 (COVID-19). Recently the US Food and Drug Administration and Centers for Disease Control and Prevention warnings of fatal cardiac toxicity from torsades de pointes (TDP) arrhythmia from HCQ receipt have been made, notwithstanding the long safe provision of HCQ to treat lupus and rheumatoid arthritis. This has resulted in restricted access of HCQ for COVID-19 treatment. We hypothesized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 36 publications
(35 reference statements)
0
25
0
Order By: Relevance
“…A recent controversial study by Prodromos et al, on the possible side effects of HCQ in patients with COVID-19 revealed that not only HCQ azithromycin is not cardiotoxic and does not cause cardiac arrhythmia and mortality, but also protect the heart with reducing cholesterol, thrombosis, and arrhythmia in the treated patients [79] .…”
Section: Antiviral Therapy For Covid-19mentioning
confidence: 99%
“…A recent controversial study by Prodromos et al, on the possible side effects of HCQ in patients with COVID-19 revealed that not only HCQ azithromycin is not cardiotoxic and does not cause cardiac arrhythmia and mortality, but also protect the heart with reducing cholesterol, thrombosis, and arrhythmia in the treated patients [79] .…”
Section: Antiviral Therapy For Covid-19mentioning
confidence: 99%
“…Given the rather cost-effective and safe outcomes from recent observational experiences with HCQ, 8,9,11,14,16,31 pending the outcomes of the ongoing clinical trials, we would propose, prepare now and implement promptly the following outline protocol for this and possibly subsequent outbreaks of COVID-19 (Figure 1).…”
Section: Dovepressmentioning
confidence: 99%
“…However, the SARS-CoV-2 load is low during early onset before massive viral replications in the body, hence only a low dose of HCQ is needed, thus better safety, without additional need for azithromycin that is known to be synergistic with HCQ or CQ for cardiac toxicity. 5 , 30 , 31 Therefore, both timing and dose appear crucial for the optimal use of HCQ in COVID-19 treatment. More recently, sequela such as fatigue, shortness of breath and headache are reported among patients three months after their recovery, even those with “mild” symptoms can suffer from COVID-19 for a long time.…”
Section: Potential Efficacy and Its Possible Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The review article by Bansal and co-workers discusses hydroxychloroquine (HCQ), which at the moment is the most widely used prophylactic and therapeutic agent for SARS-CoV-2 infection (COVID-19) in the world [ 1 ]. The safety profile of this long-utilized antimalarial/anti-inflammatory is well understood and its benefit to risk relationship is encountered everyday as physicians prescribe this agent [ 2 , 3 ]. In Figure 4, the authors depict a large white scar in the short axis image of the left ventricle similar to that of a myocardial infarction.…”
mentioning
confidence: 99%